2021
DOI: 10.2147/ppa.s312200
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Quality of Life Among Female and Male Patients with Heart Failure in Europe: A Real-World Cross-Sectional Study

Abstract: Purpose To characterize symptoms, clinical burden, and health-related quality of life (HRQoL) among women and men with heart failure (HF) with a left ventricular ejection fraction (LVEF) of ≤60% in Europe. Patients and Methods A real-world cross-sectional study was conducted in France, Germany, Italy, Spain, and United Kingdom from June to November 2019. Patient record forms were completed by 257 cardiologists and 158 general practitioners for consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
4
7
0
1
Order By: Relevance
“…The findings of this study revealed that most of the patients with third/fourth degree heart failure in Bahrain had a poor quality of life. These results are consistent with previous Fonseca et al (2021) revealed that patients with heart failure had a significantly reduced quality of life. Adebayo, Olunuga, Durodola, and Ogah (2017) review further supported the association between heart failure and poor quality of life in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study revealed that most of the patients with third/fourth degree heart failure in Bahrain had a poor quality of life. These results are consistent with previous Fonseca et al (2021) revealed that patients with heart failure had a significantly reduced quality of life. Adebayo, Olunuga, Durodola, and Ogah (2017) review further supported the association between heart failure and poor quality of life in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous published reports from other populations. For example, a large multi-national study in Europe conducted by Fonseca et al. (2021) revealed that patients with heart failure had a significantly reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although normative data are lacking, control populations of US adults identified mean productivity impairment of 6.9% to 7.1% and mean activity impairment of 14.0% to 17.3% 41,42 . Mean preoperative productivity impairment in our medically refractory CRS cohort was 34.4%, lower than that seen for Crohn disease (CD, 51.9%) but higher than that for ulcerative colitis (UC, 24.7%), chronic obstructive pulmonary disease (COPD, 24.9%), heart failure (HF, 29.1%), rheumatoid arthritis (RA, 29.1%), and asthma (15.8%‐16.8%) 43–48 . Mean activity impairment in our cohort was 36.4%, lower than that for CD (56.6%), UC (43.4%), HF (43.2%), and COPD (39.9%), but higher than for RA (33.3%) and asthma (28.1%‐28.4%) 43–48 .…”
Section: Discussionmentioning
confidence: 71%
“…41,42 Mean preoperative productivity impairment in our medically refractory CRS cohort was 34.4%, lower than that seen for Crohn disease (CD, 51.9%) but higher than that for ulcerative colitis (UC, 24.7%), chronic obstructive pulmonary disease (COPD, 24.9%), heart failure (HF, 29.1%), rheumatoid arthritis (RA, 29.1%), and asthma (15.8%-16.8%). [43][44][45][46][47][48] Mean activity impairment in our cohort was 36.4%, lower than that for CD (56.6%), UC (43.4%), HF (43.2%), and COPD (39.9%), but higher than for RA (33.3%) and asthma (28.1%-28.4%). [43][44][45][46][47][48] Evaluation among our CRS cohort identified mean 6-month productivity improvement of 20.0%, lower than posttreatment productivity improvement in RA (32.6%) and CD (21.4%), but higher than that for UC (12.6%) and asthma (2.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Cụ thể người bệnh nữ có điểm trung bình CLCS tổng thể (67,52 ± 11,80),CLCS thể chất (26,73 ± 5,07) và CLCS tinh thần (17,17 ± 4,20) cao hơn so với NB nam, có nghĩa là người bệnh nữ có CLCS tổng thể, thể chất và tinh thần kém hơn người bệnh nam. Kết quả này tương tự với kết quả của tác giả Ana và cộng sự (2021) [13] kết quả cho thấy điểm số cao hơn đáng kể (tức là CLCS kém hơn) đối với phụ nữ và nam giới (37,9 so với 34,6; p = 0,0481), CLCS liên tục cao hơn (tức CLCS kém hơn) đối với phụ nữ so với nam giới trên các lĩnh vực tính điểm về thể chất (18,6 so với 16,6; p = 0,0041) và tinh thần (9,4 so với 7,9; p = 0,0021). Đặc biệt có sự khác biệt với nghiên cứu của tác giả Lương Thị Thu Giang (2021) [8] điểm đánh giá về CLCS của NBST không có sự khác biệt giữa nam và nữ (p = 0,21).…”
Section: Liên Quan Giữa Clcs Với Một Số đặC đIểm Của đốI Tượng Nghiên...unclassified